The Indians for Indians Radio Show - Ortega, Lina (My University, 2019)
This book was published in conjunction with the exhibition Native Voices over the Airwaves: The Indians for Indians Hour Radio Show at the Bizzell Memorial Library, University of Oklahoma, from November 14, 2019 to July 3, 2020. The Indians for Indians radio show was broadcast from OU's WNAD radio station from 1941 through the mid-1970s. It was created by Don Whistler, who hosted it until 1951. After 1951, OU's Sequoyah Indian Club sponsored the program, with the assistance of Boyce Timmons, and hosted it for the remaining years at OU. Most of the tribes in Oklahoma are represented on the show, which deals with themes of community, military service, religion, education, and tribal governments and advocacy for Native rights.
Chapters: Don Whistler, the Whistler family, and a Native American connection to Campus Corner -- The Sequoyah Club -- Community life -- Military service -- Religious life -- Schools and education -- Tribal rights and tribal government -- Native languages -- The Indians for Indians legacy : our voices then continue to our voices now -- The preservation of the broadcast recordings.
Keywords: Native American Studies.; Indians for Indians (Radio program); WNAD (Radio station : Norman, Okla.); Community radio -- Oklahoma -- Norman; Indian radio stations -- Oklahoma -- Norman; Indians of North American -- Social life and customs; Whistler, Don; Sequoyah Indian Club; Timmons, Boyce